Modern aspects and trends of Customer Intelligence development - T. A. Soldatenko; S. R. Yessimzhanova (Экономика: стратегия и практика, 2020)
The current digital transformation provides great prospects for both businesses and consumers in the field of data collection and processing. The current development of data collection and processing systems opens not just new, but breakthrough opportunities for business in general and marketing in particular. Now not only structured data is being processed, but also unstructured data is becoming a part of marketing analytics.The aim of this research is to consider and present current aspects, tasks and trends of Customer Intelligence (CI) as the part of Marketing Intelligence. Today any organization can use digital tools and methods in their marketing activity. Companies have got huge ability through a lot of internal and external resources to gather and alter (processing) customer data, including personal feedback from customers. In their turn customers get more and more possibility to contact brands and companies directly. The involvement of consumers in a dialogue with a business and their influence on all areas of business activity have already become an integral part of our life.Authors did a literature review of 28 scientific and business resources to determine the nature and the role of CI in marketing activity through a prism of marketing intelligence and its four components - market, product, competitive and customers. Nowadays Customer Intelligence is one of the key marketing activity components with a huge capacity which makes a real impact on marketing performance.